2014
DOI: 10.1186/1477-7819-12-221
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection of esophageal granular cell tumor

Abstract: BackgroundEsophageal granular cell tumor (GCT) is a rare benign tumor with malignant potential. With wide application of endoscopic techniques, the esophageal GCT discovery rate and treatment strategy has changed. This study was to preliminarily evaluate outcomes of endoscopic diagnosis and treatment for esophageal GCT.MethodsFourteen patients (eight men, six women; median age, 48.5 years) with esophageal GCT diagnosed and treated by esophageal endoscopy. Esophagoscopy, endoscopic ultrasound (EUS), and endosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…Endoscopic resection of small granular cell tumors may be considered, possibly obviating the need for further surveillance. 83,84 Removal often can be accomplished by snare excision or EMR. 83,85,86 It is unknown whether small, unresected granular cell tumors or larger lesions resected endoscopically should undergo surveillance.…”
Section: Pancreatic Restsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic resection of small granular cell tumors may be considered, possibly obviating the need for further surveillance. 83,84 Removal often can be accomplished by snare excision or EMR. 83,85,86 It is unknown whether small, unresected granular cell tumors or larger lesions resected endoscopically should undergo surveillance.…”
Section: Pancreatic Restsmentioning
confidence: 99%
“…ESD has been applied for resection of carcinoid tumors, granular cell tumors, and also SELs arising from the muscularis propria. Lu et al 83 reported en-bloc resection of esophageal granular cell tumors by using ESD in 92.9% (13/14) of cases. Procedure time ranged from 25 to 60 minutes, and no adverse events were seen.…”
Section: Esdmentioning
confidence: 99%
“…Nie et al reported that, when ESD was used to treat 17 patients with esophageal GCTs, only one developed bleeding, which was managed by endoscopic hemostasis [ 33 ]. In a study by Lu et al , ESD was performed on 14 patients with esophageal GCT with no complications [ 39 ]. ESD using Clutch Cutter ® (Fujifilm Corporation, Odawara, Japan) was described with no complications for submucosal tumors that had not invaded the muscularis propria [ 26 ].…”
Section: Gastrointestinal Gcts By Locationmentioning
confidence: 99%
“…In other cases, patients presented with hematochezia, abdominal pain, loose stool or constipation [ 10 ]. When GCT involves the appendix, patients can present with appendicitis [ 39 ]. GCT can also be detected incidentally during major abdominal surgery [ 54 ].…”
Section: Gastrointestinal Gcts By Locationmentioning
confidence: 99%
“…First described by Abrikossoff 1 in 1926, GCTs are a benign entity with malignant potential that evolve from the Schwann cells of the nervous system. Principally, they can occur at any site of the human body 2, 3. About 2% of GCTs are in the esophagus4, 5; other parts of the GI system are rarely involved.…”
mentioning
confidence: 99%